Metatranscriptome-based strategy reveals the existence of novel mycoviruses in the plant pathogenic fungus Fusarium oxysporum f. sp. cubense - Ye, Yiting; Liu, Yingying; Zhang, Yifei; Wang, Xin; Li, Huaping; Li, Pengfei (Frontiers in Microbiology, 2023)
Fusarium oxysporum f. sp. cubense (Foc) is a devastating plant pathogen that caused a great financial loss in the banana’s source area. Metatranscriptomic analysis was used to determine the diversity of mycoviruses in 246 isolates of F. oxysporum f. sp. cubense. Partial or nearly complete genomes of 20 mycoviruses were obtained by BLASTp analysis of RNA sequences using the NCBI database. These 20 viruses were grouped into five distinct lineages, namely Botourmiaviridae, Endornaviridae, Mitoviridae, Mymonaviridae, Partitiviridae, and two non-classified mycoviruses lineages. To date, there is no report of the presence of mycoviruses in this pathogen. In this study, we demonstrate the presence of mycoviruses isolated from Foc. These findings enhance our overall knowledge of viral diversity and taxonomy in Foc. Further characterization of these mycoviruses is warranted, especially in terms of exploring these novel mycoviruses for innovative biocontrol of banana Fusarium wilt disease.